Melanin-like nanoparticles slow cyst growth in ADPKD by dual inhibition of oxidative stress and CREB - Yongzhan Sun; Quan Zou; Huizheng Yu; Xiaoping Yi; Xudan Dou; Yu Yang; Zhiheng Liu; Hong Yang; Junya Jia; Yupeng Chen; Shao-Kai Sun; Lirong Zhang (EMBO Molecular Medicine)
Abstract Melanin-like nanoparticles (MNPs) have recently emerged as valuable agents in antioxidant therapy due to their excellent biocompatibility and potent capacity to scavenge various reactive oxygen species (ROS). However, previous studies have mainly focused on acute ROS-related diseases, leaving a knowledge gap regarding their potential in chronic conditions. Furthermore, apart from their well-established antioxidant effects, it remains unclear whether MNPs target other intracellular molecular pathways. In this study, we synthesized ultra-small polyethylene glycol-incorporated Mn2+-chelated MNP (MMPP). We found that MMPP traversed the glomerular filtration barrier and specifically accumulated in renal tubules. Autosomal dominant polycystic kidney disease (ADPKD) is a chronic genetic disorder closely associated with increased oxidative stress and featured by the progressive enlargement of cysts originating from various segments of the renal tubules. Treatment with MMPP markedly attenuated oxidative stress levels, inhibited cyst growth, thereby improving renal function. Interestingly, we found that MMPP effectively inhibits a cyst-promoting gene program downstream of the cAMP-CREB pathway, a crucial signaling pathway implicated in ADPKD progression. Mechanistically, we observed that MMPP directly binds to the bZIP DNA-binding domain of CREB, leading to competitive inhibition of CREB’s DNA binding ability and subsequent reduction in CREB target gene expression. In summary, our findings identify an intracellular target of MMPP and demonstrate its potential for treating ADPKD by simultaneously targeting oxidative stress and CREB transcriptional activity.